Pengambilan keputusan do not resucitate pasien end of life ditinjau dari perspektif keluarga - Ridal Sagala; Hana Rizmadewi Agustina; Tuti Pahria (MEDIA ILMU KESEHATAN, 2022)
The goals of decision making process about Do Not Resuscitate orders (DNR) are supporting the autonomy of patient or family and preventing futile medical interventions. Families can experience challenges and difficulties when making decision about DNR. The exploration of the decision-making process involving family is therefore crucial. This study aimed to explore in-depth the decision making of DNR among End of Life (EoL) patients within inpatient area from the perspective of family caregiver. A qualitative descriptive phenomenology study was conducted that recruited 6 family caregivers, within purposive sampling. Data collection used in-depth interviews with face to face and video calls, and data analysis followed the Colaizzi’s method. Twelve major themes emerged from interview finding of family caregiver: decision making made through family counselling, inadequate information communication, consideration of patient health status, family’s beliefs and values, family accompaniment, time allocation, knowledge, trust in health workers, financial consideration, information provision, and needs of second opinions. The findings of this study highlighted providing communication and sharing information were ineffective and inadequate. Several barriers factors were also found related to culture and religious beliefs and values, lack of knowledge and formal training, time constrains, caring experience, and financial consideration. Conclusion thus suggest need to inprove their ability to provide adequate information, to sharing and to perform an effective communication. Assessing appropriate and providing standards of operational procedure is essential to be done in order to improve communication styles and facilitate a shared decision making, partculary in DNR decision making for EoL patients.